2021
DOI: 10.1007/s10803-021-04903-2
|View full text |Cite
|
Sign up to set email alerts
|

Episodic Future Thinking in Autism Spectrum Disorder and 22q11.2 Deletion Syndrome: Association with Anticipatory Pleasure and Social Functioning

Abstract: Episodic future thinking (EFT) has been suggested to underlie anticipatory pleasure (AP), itself known to play a crucial role in social functioning (SF). Both AP and SF are impaired in various clinical populations, including autism spectrum disorders (ASD) and 22q11.2 deletion syndrome (22q11DS). Therefore, the relationship between EFT, AP and SF was investigated, as well as the potential role of projecting oneself in a social vs. non-social context. Seventy-seven participants [24 with 22q11DS, 20 with ASD, 33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 72 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…Indeed, it has been shown that not only identifying one’s own emotional states ( Barrett et al, 2001 ) but also predicting one’s emotions during future events ( Werner & Gross, 2010 ) appears to be important for effective regulation of emotions. Difficulties in episodic future thinking, associated with reduced anticipatory pleasure, have been reported in some adolescents and young adults with autism ( Feller et al, 2021 ). On the contrary, as the current study only examined cognitive ER, it is likely that youth also used other types of adaptive or non-adaptive strategies to (directly or indirectly) regulate their emotions, which were not captured.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that not only identifying one’s own emotional states ( Barrett et al, 2001 ) but also predicting one’s emotions during future events ( Werner & Gross, 2010 ) appears to be important for effective regulation of emotions. Difficulties in episodic future thinking, associated with reduced anticipatory pleasure, have been reported in some adolescents and young adults with autism ( Feller et al, 2021 ). On the contrary, as the current study only examined cognitive ER, it is likely that youth also used other types of adaptive or non-adaptive strategies to (directly or indirectly) regulate their emotions, which were not captured.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that not only identifying one's own emotional states (Barrett et al, 2001) but also predicting one's emotions during future events (Werner & Gross, 2010) appears to be important for effective regulation of emotions. Interestingly, impaired episodic future thinking, associated with reduced anticipatory pleasure, has been reported in adolescents and young adults with ASD (Feller et al, 2021).…”
Section: Emotion Regulationmentioning
confidence: 97%
“…Since this identification with one’s future self is crucial for significant life possibilities, corresponding difficulties will also affect one’s capacity for hoping. In particular, recent findings suggest that autistic people often have difficulties with episodic future thinking, or future-oriented mental time travel ( Feller et al, 2021 ; Ye et al, 2023 ). Inasmuch as impairments of episodic future thinking have been linked to depression ( Hallford et al, 2018 ), a close connection with fundamental hopelessness seems likely.…”
Section: Dimensions Of “Black Pill” Hopelessness – ...mentioning
confidence: 99%